Moisture sensitive inimitable Armalcolite/PDMS flexible sensor: A new entry - Tripathy, Ashis; Sharma, Priyaranjan; Sahoo, Narayan; Pramanik, Sumit; Abu Osman, Noor Azuan (Elsevier, 2018)
Armalcolite, a pioneering material which is commonly available on the moon surface, was synthesized first time in the laboratory environment using innovative solid-state-step sintering process. Afterwards, Armalcolite/Polydimethylsiloxane (PDMS) nanocomposite was prepared using ball milling technique and then spin coated on interdigitated customized gold (Au) electrode on a polyimide substrate in order to develop a high sensitive and fast-response flexible humidity sensor. To evaluate the performance of developed flexible humidity sensor, the electrical characterization was performed at room temperature of 25 °C in a humidity environment of 33–95% RH using alternating current. The developed sensor exhibits an exceptional performance in terms of high sensitivity, good linearity, negligible hysteresis (<1%), better response and recovery time of 10 s and 15 s respectively, which is outstanding when compared with existing ones within the same category. The long-term stability of flexible sensor was confirmed upon when it was put into test for 30 consecutive days. Due to its grater flexibility, low hysteresis, high stability and the fast response/recovery time, it is intended to use for various application in modern industry, agriculture, and medical care where humidity plays a crucial role.